Analisis Faktor-Faktor yang Mempengaruhi Efektivitas Penegakan Hukum Terhadap Korupsi Berdasarkan UU No. 1 Tahun 2023 - Maura Viranti; Pradipta Larasati; Rain Victoria; Taun Taun (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2025)
Corruption is a serious problem that hampers the development process and creates social and economic instability in Indonesia. In an effort to tackle increasingly disturbing criminal acts of corruption, the Indonesian government has taken concrete steps by enacting various regulations, one of which is Law Number 1 of 2023 concerning Law Enforcement Against Corruption. This research aims to conduct an in-depth analysis of various factors that influence the effectiveness of law enforcement against corruption, especially in the context of implementing Law no. 1 of 2023. In order to achieve this goal, this research uses a qualitative approach with descriptive analysis methods, which aims to thoroughly understand the role and influence of this law on improving the quality of law enforcement against criminal acts of corruption. Several factors analyzed in this research include institutional aspects involved in law enforcement, the quality and competence of human resources, the law enforcement policies implemented, as well as various challenges and obstacles faced by law enforcement officials in implementing this law effectively. Through this analysis, it is hoped that this research can provide deeper insight into the effectiveness of the implementation of Law no. 1 of 2023 in overcoming corruption, as well as providing constructive recommendations to improve the law enforcement system in Indonesia to achieve more optimal results in eradicating corruption.